The relationship between non-fatal overdose of pharmaceutical medications, suicidality and depression - Buykx, Penelope (Curtin University, 2007)
This thesis examines three main themes; depression, suicidality, and non-fatal overdose involving pharmaceutical and over-the-counter (OTC) medications. At any given time depression affects approximately one in every twenty adults in Australia. People with depression are at elevated risk of attempted and completed suicide compared to those without. Medication overdose is a frequently chosen method of suicidal behaviour, and accounts for one in ten suicide deaths and close to nine out of ten non-fatal episodes of suicidal behaviour for which hospital treatment is sought. The study reported here had six primary aims; (i) to quantify medication overdose presentations over a 12-month period to the Emergency Department (ED) of a major metropolitan public hospital in Melbourne, Australia, (ii) to describe the medication overdose patient group, including comparison with two other relevant types of presentation, illicit drug overdose, and actual or potential self-harm by means other than overdose, (iii) to explore the relationship between depression, suicidal ideation and medication overdose, (iv) to identify the medications typically used in overdose and their means of acquisition, (v) to explore patient experiences of emergency care following a medication overdose, and (vi) to comment on the feasibility of introducing a brief intervention within the ED with the intention of addressing the issue of medication overdose. Three data sources were employed: computerised ED records, interviews with a sub-sample of patients attending the ED following a medication overdose, and observation of ED processes in relation to these cases.One of the most important findings of the study was the large contribution made by benzodiazepine medications to the overall medication overdose statistics. When considered in conjunction with the patient interview data, it appeared that many patients included in the study were prescribed benzodiazepines in a manner that contradicts current national prescribing guidelines. The problem of medication overdose could be partially addressed by working with doctors to ensure the appropriateness of their prescribing practices, to encourage them to more closely monitor the treatment progress of at-risk patients, and to increase awareness of other evidence-based forms of treatment for depression and anxiety.